Water availability dynamics have long‐term effects on mature stem structure in Vitis vinifera. Issue 9 (31st August 2018) - Munitz, Sarel; Netzer, Yishai; Shtein, Ilana; Schwartz, Amnon
Abstract : Premise of the Study: The stem of Vitis vinifera, a climbing vine of global economic importance, is characterized by both wide and narrow vessels and high specific hydraulic conductivity. While the effect of drought stress has been studied in 1‐ and 2‐yr‐old stems, there are few data documenting effects of drought stress on the anatomical structure of the mature, woody stem near the base of the vine. Here we describe mature wood anatomical responses to two irrigation regimes on wood anatomy and specific hydraulic conductivity in Vitis vinifera Merlot vines. Methods: For 4 years, irrigation was applied constantly at low, medium, or high levels, or at alternating levels at two different periods during the growing season, either early spring or late summer, resulting in late season or early spring deficits, respectively. The following variables were measured: trunk diameter, annual ring width and area, vessel diameter, specific hydraulic conductivity and stem water potential. Key Results: High water availability early in the season (late deficit) resulted in vigorous vegetative growth (greater trunk diameter, ring width and area), wider vessels and increased specific hydraulic conductivity. High water availability early in the season caused a shift of the vessel population towards the wider frequency classes. These late deficit vines showed more negative water potential values late in the season than vines that received low but relatively constant irrigation. Conclusions: We concluded that high water availability during vegetative growth period of Vitis increases vessels diameter and hydraulic conductivity and causes the vines to be more vulnerable to drought stress late in the season.